Value Added Tax (VAT) Accounting Treatment at Gold Shops and Fiscal Financial Statements Its Impact on Gold Shops Asli Jaya Asli Setia Cakranegara Timur - Salsabina, Elsa Thalia; Pusparini, Herlina (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to analyze the accounting treatment of Value Added Tax (VAT) in gold shops and its impact on fiscal financial statements, especially in Toko Emas Asli Jaya Asli Setia in East Cakranegara. The research method used is a case study with a qualitative descriptive approach. Data was collected through interviews, observations, and documentation which were then analyzed in depth to get an idea of how VAT treatment affected the financial performance of the gold store. The results of the study show that the proper application of VAT accounting in accordance with the provisions of applicable tax regulations has a great influence on the financial performance of gold stores. VAT treatment affects the cost structure, profit margins, and tax liabilities which ultimately impacts the profitability and liquidity of gold stores. Implementing an effective strategy in VAT management can help gold shops comply with tax regulations and optimize their financial performance.